Penentuan Keadaan Insolvensi terhadap Proses Kepailitan dalam Undang-Undang Nomor 37 Tahun 2004 Tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang - Shelomita Putri Amelia; Ema Nurkhaerani (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Bankruptcy regulations in Indonesia, particularly in Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, are often contentious due to the absence of strict limitations on the filing of bankruptcy petitions. This has the potential to ensnare debtors who are still financially solvent, overriding the principle that bankruptcy should be the last resort in debt settlement. Law Number 37 Year 2004 on Bankruptcy and Suspension of Debt Payment Obligations only requires the existence of two creditors with debts that are due and collectible through simple proof. This study aims to analyze in depth the legal arrangements and determination of insolvency in Law Number 37 of 2004. By using a normative juridical research method, as well as a statute approach that focuses on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations and other related regulations, secondary data will be collected through literature studies. Insolvency is defined as a condition where the debtor's total debt to all creditors exceeds the value of all its assets, otherwise known as a state of inability to pay. In Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, the term "insolvency" differs from commonly used terms, such as balance sheet insolvency, which means debts exceeding assets, or cash flow insolvency, which means the inability to pay debts due to liquidity. Unlike the practice in the common law system, the determination of insolvency in Indonesia does not involve mandatory financial audits or court decisions based on independent financial analysis.